2021
DOI: 10.1007/s13592-021-00845-x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond brood: the potential impacts of insect growth disruptors on the long-term health and performance of honey bee colonies

Abstract: Honey bees are valued pollinators of agricultural crops, and heavy losses reported by beekeepers have spurred efforts to identify causes. As social insects, threats to honey bees should be assessed by evaluating the effects of stress on the long-term health and productivity of the entire colony. Insect growth disruptors are a class of pesticides encountered by honey bees that target pathways involved in insect development, reproduction, and behavior, and they have been shown to affect critical aspects of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 140 publications
(217 reference statements)
0
11
0
Order By: Relevance
“…For many compounds, much lowered concentrations have been observed in larval queen diet following colony exposure (Böhme et al, 2018), and developing workers only receive a small amount of pollen in their diet in the latter days of larval development (Haydak, 1970), suggesting that larvae are at much lower exposure risk through diet relative to adults. It is not known how prevalent IGD residues are in royal jelly, but numerous studies have shown profound impacts on larvae following colony exposure, suggesting that IGDs do translocate to larval diet at appreciable concentrations, albeit when colonies are directly exposed to heavily contaminated food sources [as reviewed in Fine and Corby-Harris (2021)]. Furthermore, beekeepers frequently report heavy brood loss following almond pollination, where IGDs, along with other agrochemicals, are often applied directly to blooming crops (Pollinator Stewardship Council, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many compounds, much lowered concentrations have been observed in larval queen diet following colony exposure (Böhme et al, 2018), and developing workers only receive a small amount of pollen in their diet in the latter days of larval development (Haydak, 1970), suggesting that larvae are at much lower exposure risk through diet relative to adults. It is not known how prevalent IGD residues are in royal jelly, but numerous studies have shown profound impacts on larvae following colony exposure, suggesting that IGDs do translocate to larval diet at appreciable concentrations, albeit when colonies are directly exposed to heavily contaminated food sources [as reviewed in Fine and Corby-Harris (2021)]. Furthermore, beekeepers frequently report heavy brood loss following almond pollination, where IGDs, along with other agrochemicals, are often applied directly to blooming crops (Pollinator Stewardship Council, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These ubiquitous and interacting stressors have been shown to negatively affect various aspects of honey bee health including larval and pupal development (Wu et al, 2011;Chen et al, 2016), longevity (Wu et al, 2011;DeGrandi-Hoffman and Chen, 2015), immune function (Nazzi and Pennacchio, 2018;Harwood and Dolezal, 2020), and memory (van Dame et al, 1995;Siviter et al, 2018). Perhaps one of the more troubling and cryptic effects of these stressors relate to disruptions in the performance of important honey bee social behaviors and alterations to the expected pattern of temporal polytheism (Tasei, 2001;Thompson et al, 2007;Fine and Corby-Harris, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This restriction prevents the insect from forming a new epidermis after molting, preventing the insect from molting or deforming 26 . Contact and oral tests have shown that chlorbenzuron has no lethal effect on adult bees 27 . Currently, chlorbenzuron is widely used in agriculture to control insect pests of vegetables, rapeseed and other crops.…”
Section: Introductionmentioning
confidence: 99%
“…26 Contact and oral tests have shown that chlorbenzuron has no lethal effect on adult bees. 27 Currently, chlorbenzuron is widely used in agriculture to control insect pests of vegetables, rapeseed and other crops. Chlorothalonil is a widely used fungicide with good adhesion.…”
Section: Introductionmentioning
confidence: 99%